Sexual selection in the cricket Gryllus bimaculatus: no good genes? - Rodríguez-Muñoz, R; Bretman, A; Hadfield, J; Tregenza, T (2008)
Recent studies have suggested that females of the field cricket Gryllus bimaculatus exercise post-copulatory choice over the paternity of their offspring. There is evidence that these choices are made in relation to the genetic compatibility of mates rather than their absolute quality, but the magnitude of heritable differences in males has not been thoroughly examined. Using a half-sib breeding design we measured additive genetic variance and dam effects in a suite of reproductive and non-reproductive traits. Both components explained relatively little of the phenotypic variance across traits. The dam component in our design contains variance caused by both maternal effects and dominance. If maternal effects are negligible as suggested by previous studies, our data suggest that dominance variance is an important source of variation in these traits. The lack of additive genetic variation, but possible existence of large amounts of non-additive genetic variation is consistent with the idea that female mate choice and multiple mating may be driven by differences in genetic compatibility between potential mates rather than by differences in genetic quality.